Analisis Efisiensi Rantai Pasok Lateks dengan Metode Data Envelopment Analysis (DEA) di PT Perkebunan Nusantara IX Kebun Krumput Banyumas - Wardoni, Ilham; Putri, Dindy Dharmawati (Universitas Galuh, 2024)
Every company is required to achieve an optimal level of efficiency. Efficiency is ability to use resources (inputs) to achieve a certain amount of output. Supply chain performance efficiency can determine which input supply units are efficient or inefficient. PTPN IX Kebun Krumput Banyumas has a latex supply chain to produce export quality natural rubber. The purpose of this study was to determine and assess the efficiency of latex supply chain performance of each unit three afdeling in Krumput garden. The analytical method used is Data Envelopment Analysis (DEA), a linear program-based technique to measure the efficiency of a unit. The results show the Tumiyang afdeling is afdeling has the most efficient DMUs, namely 3, while the Krumput and Kubangkangkung afdeling have only one each. Overall, the efficiency performance of three afdeling supply chains is quite good as shown by the total average efficiency value of 0.81454.